Intergenerational Transmission of Work Values in Czech Republic, Spain, and Turkey: Parent-Child Similarity and the Moderating Role of Parenting Behaviors. Issue 1 (March 2019) - Sümer, Nebi; Pauknerová, Daniela; Vancea, Mihaela; Manuoğlu, Elif
Although public debates emphasize a weakening of work values and ethics over the last few decades, little attention has been paid to the transmission of work values between parents and children. It is still unclear what kind of parental behavior is critical and if culture influences the intergenerational transmission of work values. Based on socialization and value transmission theories, we explore the question by comparing three countries with different cultural characteristics: Czech Republic, Spain, and Turkey. We used data from the CUPESSE project collected from young adults aged 18 to 35 and their parents. Turkish young adults and parents reported higher levels of moral- and gender-based work values than their Spanish and Czech counterparts. Parent-child similarity in work values was the highest among the Turkish families and the lowest among the Czech families. Overall, we find that stronger moral and redistributive work values and weaker gender role–based work values are associated with high levels of parental warmth and autonomy granting and low levels of perceived psychological control. Results suggested that family climate, rather than specific paternal and maternal parenting behaviors, have more substantial effect on the value transmission. We discuss implications that consider the role of cultural orientation and gender roles.